Investigation of Bacterial and Fungal Spp. Causing Vaginal Infection in Married Libyan Women Attending Gynecology Clinics in Aljmail City - Rumadhanah Abraheem Mohammed; Zakeeyah Saliam Mohammed Qajjam; Kareemah Murajia Mohammed (African Journal of Advanced Pure and Applied Sciences, 2023)
Because the vaginal microbiome changes and is susceptible to a variety of pathogenic bacteria, treating vaginal infections in married women seeking gynecological treatment is difficult. These infections, mostly bacterial and fungal, cause significant pain and damage women's health and quality of life. This study examines sociodemographic characteristics, pregnancy status, medical conditions, vaginal hygiene behaviors, and bacterial and fungal species to better understand their effects on vaginal health. Understanding these traits is essential to developing effective therapy and prevention measures for these diseases. This cross-sectional study examined married women attending gynecological clinics in Al-Ajmal, Libya. Social demographics, pregnancy status, medical issues, and vaginal cleaning practices were collected using structured questionnaires. Standard laboratory techniques were used to test vaginal samples for bacteria and fungi. Then, the data was evaluated to determine the prevalence of microorganisms and sociodemographic features in participant women. The study findings indicated that there was a greater percentage of older women, residing in rural areas, and had lower levels of education and income who sought gynecological care. Diverse instances of bacterial and fungal species, specifically Escherichia coli and Candida albicans, were detected, hence emphasizing their involvement in vaginal infections. Variations in the frequencies of vaginal wash behaviors were noted among the subjects. This study shows the various aspects that affect vaginal health in married women. Customized interventions targeting sociodemographic gaps, hygiene practices, and medical conditions are needed to manage and prevent vaginal bacterial and fungal infections. Understanding this topic is crucial to improving women's vaginal health.